The most appropriate mixing method of polypropylene fiber with aggregates and bitumen based on binder mix design - Zahedi, Mohsen; Bayat, Ramin; Nazemi Jalal, Mehdi (International Journal of Engineering and Technology, 2014)
Asphalt is used in road pavements as the binder of aggregates in a great extent all around the world. Asphalt Modifiers have used in pavement engineering in order to enhance the physical and mechanical properties of asphalt mixtures. One of the most important of them is Polypropylene Fiber that causes increasing stability in the mixture. In this article usage of this fiber in civil engineering and especially in asphalt mixtures is investigated; Mixing methods of fiber with aggregates and bitumen are dry, wet and complex are investigated and the most appropriate method because of homogenous mixing and better result is introduced. Keywords: Polypropylene Fiber, Mixing, Bitumen, Aggregates, Binder.